2022
DOI: 10.1109/access.2022.3178811
|View full text |Cite
|
Sign up to set email alerts
|

Design of Anti-Eavesdropping Scheme for SLT-LT Codes Based on Random Symbol Sets

Abstract: In recent years, physical layer security technology has provided a new way to solve the problem of secure transmissions in wireless communications from an information theory perspective by using physical layer security coding and the inherent characteristics of the channel. As a nonsystematic code, Luby transform (LT) code has the characteristics of random coding and rateless, therefore, eavesdroppers cannot directly obtain useful information from leaked code symbols. As a shifted LT (SLT) code, the SLT codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Ref. [ 22 ] applied the SLT code to the Wyner channel model for research, and found that the value of would affect the system decoding overhead and eavesdropper error rate. The bit error rate of the eavesdropper shows a sawtooth change with the increase in , and the peak value of the sawtooth gradually decreases.…”
Section: Slt Code and Degree Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ref. [ 22 ] applied the SLT code to the Wyner channel model for research, and found that the value of would affect the system decoding overhead and eavesdropper error rate. The bit error rate of the eavesdropper shows a sawtooth change with the increase in , and the peak value of the sawtooth gradually decreases.…”
Section: Slt Code and Degree Distributionmentioning
confidence: 99%
“…Ref. [ 22 ] pointed out that when SLT is used as the secure coding method, the bit error rate of the eavesdropper is higher when the legitimate receiver receives and transferred information symbols. When , the SLT code degenerates into the traditional LT code.…”
Section: Slt Code and Degree Distributionmentioning
confidence: 99%
See 3 more Smart Citations